Pleural adenosine deaminase estimation: A Potential marker to distinguish between tubercular and non-tubercular effusion - Anil C. Byakod; M.S. Biradar (Al Ameen Medical College, 2018)
Background: Tuberculosis is a common cause of pleural effusion in countries like India where it is highly endemic. The biochemical markers are more sensitive and reliable in the diagnosis of pleural tuberculosis. Objectives: The present study was aimed to evaluate the diagnostic potential of pleural adenosine deaminase levels in tubercular pleural effusion. Materials and Methods: The study is a clinical, prospective and observational of 50 patients of pleural effusion consecutively admitted in the medical wards. Detailed history, thorough physical examination, radiological findings, haematological and biochemical findings were recorded in the proforma. Pleural aspiration was performed on all patients. Macroscopic findings, cytological, microbiological and biochemical analysis of pleural fluid were performed in all patients including pleural adenosine deaminase level. Results: Mean age group of tubercular effusion was 26-55 years and common in men. Out of 31 tubercular effusion patients, 29 (93.33%) were showed pleural adenosine deaminase level more than 40IU/L. pleural adenosine deaminase estimation showed 93.3% sensitivity and 90% specificity, 93.3% positive predictive value and 90% negative predictive value. Mean pleural adenosine deaminase level (IU/L) in tubercular, synpneumonic and transudative effusions were 70.36±26.48, 17.46±4.31 and 11.58±2.35 respectively. Conclusions: Pleural adenosine deaminase estimation seems to have the potential for being one of safe, simple, reliable and noninvasive marker which is adequately sensitive and specific in distinguishing tubercular and non tubercular effusion.